Community health nurses' HIV health promotion and education programmes: A qualitative study - M. Abe (2018)
© 2014 International Council of Nurses. Background: Globally, nurses practice in many settings with people with human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS), taking an increasing share of the professional burden of care and helping to reduce morbidity and mortality. International literature is sparse about Thai community nurses providing primary healthcare programmes for people with HIV. Aim: This study aimed to describe background, experiences and strategies of community nurses regarding their design and delivery of programmes for people living with HIV and AIDS in Chiang Mai Province, Thailand. Design: This study used a qualitative mixed-methods study employing a qualitative survey and in-depth interviews. Methods: Twenty community health nurses from 18 small community hospitals completed a survey comprising demographic data and 13 open-ended questions. Four of them later engaged in in-depth interviews using the same questions. Survey, interview data and field notes were analysed using interpretive content analysis. Findings: Four themes and six sub-themes portrayed participants' rich experiences and knowledge of HIV health promotion and education; challenges of daily work, discrimination and ethical issues; success through programme diversity comprising promotion of community volunteerism, networking and relationships; and holistic connections with Thai cultural traditions and Buddhism. Conclusions and implications for practice: Findings help to recognize the diversity, uniqueness and contributions of Thai community nurses regarding culturally appropriate health promotion and education programmes for people living with HIV and AIDS. Findings inform nurses and health officials in and outside of the country to complement innovation in future HIV health promotion and education programmes. Limitations: Our sample came from one province of Thailand. Findings might not be reflective of nurses elsewhere. Implications for health and nursing policy: Three decades of collective experience in providing holistic and multifaceted HIV and AIDS nursing care, education and health promotion by community health nurses have the potential to effect new and existing policies and protocols on HIV community care in Thailand, but more research is required for this.